Penerapan “Civic Journalism” PR FM Dalam Membangun Iklim Demokrasi di Jawa Barat - Roni Tobroni (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2018)
Civic journalism is one concepts of journalism that seeks to build public participation in the democratic process through mass media channels. This research aims to explore the civic journalism applied by PR FM in West Java with the concept of civic journalism. This study uses a case study method with data collection techniques in the form of in-depth interviews and observations. This study found the efforts of PR FM in building civic journalism with the concept of citizen journalism has been starting since its inception. PR FM from the beginning continued to campaign the importance of public involvement. Initially, PR FM gave an example, now that involvement is very high, so many public problems has resolved. Uniquely, PR FM is able to become a close friend to the listeners by becoming a place to sharing personal matters. PR FM intelligently positions itself as an active information bridge to direct every incoming content and aspiration.